Islamic Education Model in Non-Formal Institutions ADAPTATION IN THE ERA OF ACCELERATION OF INFORMATION TECHNOLOGY - ., Mahsun (TAWASUT, 2024)
Abstract This literature research looks at the history of Islamic education in Indonesia starting at the same time as the process of entering Islam in Indonesia by taking the form of non-formal education with the most prominent feature being the concentrated subject matter for the development and deepening of religious sciences such as monotheism, fiqh, tasawuf, morality, interpretation, and hadith. The learning is concentrated on the discussion of the yellow books (classic). The methods are sorogan, wetonan and muzakarah (consultation). The system is non-classical, namely by using the halaqah system. And in this era of accelerating information technology (third millennium) the survival of non-formal Islamic education has challenges in quality, culture and competition. The results show that the adaptation of non-formal Islamic educational institutions as an educational model can take the form of updating the quality of the education component, applying religious values to operational values, and updating the quality so that non-formal Islamic education is not abandoned by the community. Keywords: model, Islamic education, non-formal education